Becoming Plastic, Transforming Justice - Willlis Jenkins (Journal of Moral Theology, 2025)
The author discusses how, in early Christian thought, the word ‘plastic’ indicated the human ability of being molded by divine action. Then, plastic became emblematic of the human capability to pollute and of colonial, dominating powers over human beings and the Earth. Ethically, we should retrieve the original meaning and assume our responsibility, caring for our planet. By engaging the Minderoo-Monaco Report, the author highlights six approaches which could turn plastics and their impacts into ethical problems that could be tackled: trash containment, bodily contamination, violence and injury, distributive injustice, multispecies injustice, colonial injustice and integrative repair. The chapter ends by commenting on five tactics which could guide our actions: cap production, inclusive science, extended producer responsibility, rights of rivers and oceans, and living a good life with plastic.